The Importance of Character Education in the Digital Era for the Future - Slamet Pamuji; Samantha Gonzales; Ali Reza (Yayasan Adra Karima Hubbi, 2024)
This research aims to describe the importance of character education in this digital era for the future. This research is qualitative, descriptive and internet searching research. Basically, education is an effort to improve human resource capabilities so that they have character and can live better independently. Character education is a process of applying moral and religious values ??to students through knowledge, applying these values ??both to oneself, to fellow friends, to educators, and to God Almighty. The demand for education to produce quality students continues to be raised so that the whole community is aware that education is important in this digital era. Basically, all the problems that occur at the educational level include religious, national, mutual cooperation, integrity and independence for students. Looking at current developments, many children in society use technology as entertainment, lack morals and have bad social behavior. Therefore it is necessary to develop a sense of responsibility. So as to form a competent generation. The digital era not only has positive impacts but also negative impacts, and the task of educators, parents and adults is to guide and monitor children's behavior in using digital media, so that children can make maximum use of digital media and obtain the maximum benefits. Good for himself and his life.